Exploration of Ethnomathematics in Batik Pandanwangi as a Source of Contextual Learning - Sugiarni, Rani; Sari, Widya; Adetia, Elsa; Azmy, Dara Septia (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Ethnomathematics can serve as a bridge between school mathematics learning and everyday culture. Mathematical concepts found in cultural artifacts can be used as learning resources, allowing students to gain two or more types of knowledge simultaneously, at least in terms of culture and mathematics. Cianjur Regency is famous for Pandanwangi rice, known for its distinct fragrance. The uniqueness of Pandanwangi rice is expressed in batik. This study aims to explore the ethnomathematics present in Pandanwangi Batik, which can be utilized as a learning resource for teaching mathematical concepts. A qualitative research approach with an ethnographic method was employed to explore the mathematical concepts embedded in Pandanwangi Batik. Data were collected through observation, in-depth interviews with traditional confectionery makers, and documentation of the production process. The study used a human instrument, where the researcher directly acted as the data collector by interacting with the research environment. Data collection techniques included observing the activities of batik-making, conducting interviews to understand cultural and mathematical aspects, and documenting patterns and processes involved. The research findings indicate that Pandanwangi Batik contains various ethnomathematical concepts, including proportions (e.g., proportionality, equivalent ratios, inverse ratios), number patterns, geometry, geometric transformations (translation, reflection, rotation), and social arithmetic. These mathematical concepts are derived from the production process, crafting techniques, patterns, and sales outcomes of the batik.